Decision-Making Data: Expectations for Reproducibility of Lifting on Separate Days. Issue 4 (July 2018) - Swift, Marcie C.; Townsend, Robert; Edwards, Douglas W.; Loudon, Janice K.
Abstract : Purpose: The purpose of this study was to explore the difference in maximal lifting capability between 2 modes of lifting (traditional crate and XRTS Lever Arm) over multiple days. The differences in absolute strength values were compared with existing criteria for sincere effort during distraction-based lifting. In addition, rate of perceived exertion (RPE) is presented for the 2 modes of lifting on each day. Primary Practice Setting: Workers' compensation. Methodology and Sample: Forty-four subjects between the ages of 20 and 44 years participated in this study. Investigators established 1 repetition maximum (RM) for each subject performing the crate lift. Subjects were randomly assigned 5 weights ranging from 10% to 100% of their determined 1RM and asked to give their rating of perceived exertion after each lift. The same procedure was repeated 2–5 days later using the XRTS Lever Arm. Paired t tests and Spearman's correlation coefficient were used for data analysis. Alpha was set at less than .05. Results: There was a statistically significant difference ( p < .04) between maximal lift values for the 2 lifting modes. The percent difference between the modes of lifting was 10.5% ± 6.4%. In addition, there was a positive correlation between the RPE on the 2 modes of lifting ( p = .87). Implications for Case Management Practice: A functional capacity evaluation (FCE) is typically ordered after the completion of physical rehabilitation and before releasing a patient to full or modified duty. In addition to assessing the ability to function within normal job demands, an assessment of effort by the participant typically takes place during an FCE. Case managers and physicians are presented with information, allowing them to make comparisons between functional lifting abilities displayed during treatment sessions and the FCE. These comparisons may often take place with the subpoena of medical records and may be discussed during the deposition or trial process. If an FCE takes place at a different facility than the physical therapy or work conditioning treatment, 2 different modes of lifting may take place based on the equipment within each facility. The results of this study indicate that the 2 modes of lifting on separate days meet established criteria for lift comparison testing during FCEs.